Regional coherency of boreal forest growth defines Arctic driftwood provenancing - Hellmann, Lena; Agafonov, Leonid I.; Churakova, Olga V.; Düthorn, Elisabeth; Eggertsson, Ólafur; Esper, Jan; Kirdyanov, Alexander V.; Knorre, Anastasia A.; Moiseev, Pavel A.; Myglan, Vladimir S.; Nikolaev, Anatolii N.; Reinig, Frederick; et al. (Dendrochronologia, 2016)
ISSN:1125-7865 ISSN:1612-0051